The Impact of Logistics Infrastructure on the Development of Intermodal Transport - Błocisz, Natalia (Towards Sustainable Transport in Logistics and International Trade, 2025)
The purpose of the chapter is to present the key aspects of logistics infrastructure and its significance for intermodal transport. The study aimed to assess the impact of well-developed transport infrastructure on the efficiency of logistics processes, including route optimization, reduction of delivery times, and cost minimization. The results indicate that high-quality transport infrastructure facilitates the integration of different transport systems, reducing operational costs and environmental impact. Respondents from both logistics companies and the transport sector identified the expansion of road networks and logistics warehouses as critical factors for the development of intermodal transport. Moreover, most respondents pointed to the need for investment in modern technologies and route optimization to enhance the efficiency of this type of transport. The study has practical relevance in the context of intermodal transport development and increasing the competitiveness of companies and the economy as a whole.